Effect of particle size on mixed-mode fracture of nanographene reinforced epoxy and mode I delamination of its carbon fiber composite. (1st December 2017) - Roy, Samit; Kumar, Abhishek
Abstract: Motivated by the lack of available mixed-mode test data in the literature on graphene nanocomposites, this article aims to investigate two cases: (a) the changes in mixed-mode fracture properties of a thermoset polymer (EPON 862) reinforced with hydrogen passivated nanographene platelets (HP-NGPs) and, (b) Mode I fracture properties of EPON 862/IM7 unidirectional laminate with dispersed HP-NGPs. For case (a), mixed mode fracture experimentation was performed using an asymmetric four-point bending specimen on baseline (0 wt%), 0.1 wt% and 0.5 wt% HP-NGP reinforced EPON 862. Three different mode mix (KII /KI ) ratios (0.78, 1.53, 117) were used to obtain a fracture envelop encompassing pure Mode I to Mode II. Remarkable increases in the fracture envelop both in Mode I (3 times) and Mode II (2.5 times) was observed with only 0.5 wt% of HP-NGP. For case (b), Double Cantilever Beam (DCB) experiments were used to obtain the fracture toughness of the unidirectional IM7/EPON 862 laminates with the HP-NGP reinforced matrices. Significant increase (100%) in resistance to crack propagation in DCB specimens was observed. A brittle to ductile transition at the crack tip due to a novel nanoscale size effect is postulated and verified using TEM as the reason for the toughness increase.